2022
DOI: 10.1002/jip.1608
|View full text |Cite
|
Sign up to set email alerts
|

Who lives, who dies, who decides: Differences between mass public shooters who survive, are killed, and commit suicide

Abstract: This study provides an in-depth analysis of American mass public shooting conclusions between 1966 and 2017. Specifically, this work examines differences in factors contributing to the perpetrator's likelihood of surviving, being killed, and committing suicide. Ten hypotheses, rooted in previous homicide, suicide, homicide-suicide, and mass public shooting literature consider different psychological, situational, and background factors shaping the outcome of mass public shootings. Significant findings indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Those with higher victim counts also distinguished those who were killed from those who survived. Being killed was also associated with arrival of law enforcement, resistance, and government targets, the latter presumably due to increased security [44]. In comparing with our study, it would appear that the larger the victim count (10 or more homicides for massacre homicides), differences between the groups dissolve, although history of suicidal ideation may simply have not been accessed uniformly.…”
Section: Extra‐familial Homicide‐suicidementioning
confidence: 56%
See 2 more Smart Citations
“…Those with higher victim counts also distinguished those who were killed from those who survived. Being killed was also associated with arrival of law enforcement, resistance, and government targets, the latter presumably due to increased security [44]. In comparing with our study, it would appear that the larger the victim count (10 or more homicides for massacre homicides), differences between the groups dissolve, although history of suicidal ideation may simply have not been accessed uniformly.…”
Section: Extra‐familial Homicide‐suicidementioning
confidence: 56%
“…Capellan and colleagues [44] trichotomized as we did, and found that those who committed suicide were associated with suicidal ideation, higher numbers of victims, and evidence of suicide imitation of others. Those with higher victim counts also distinguished those who were killed from those who survived.…”
Section: Autogenic Stranger Mass Homicide-suicidementioning
confidence: 64%
See 1 more Smart Citation
“…According to Duntley and Buss [4], “homicide ideation is part of an evolved psychological process that functions to mobilize attention, rehearse scenarios where homicide is a behavioral option, calculate the consequences of it, and motivate behavior” [2, p. 555]. Suicidal ideation is significantly associated with completed suicide: Relevant to homicide‐suicide, in mass public shooters suicidal ideation is associated with perpetrators who take their own lives in contrast to those interdicted, shot and killed by law enforcement [5].…”
Section: Introductionmentioning
confidence: 99%